Effect of local thermal non-equilibrium on thermoporoelastic response of a borehole in dual-porosity media. (September 2018) - Li, Wenda; Chen, Mian; Jin, Yan; Lu, Yunhu; Gao, Jiajia; Meng, Han; Zhang, Yayun; Tan, Peng
Highlights: Heat transfer coefficient was calibrated by modified K-C equation. LTNE occurs due to insufficient heat transfer caused by large fracture spacing. Thermoporoelastic solution of a borehole considering LTNE was derived. Temperature difference induces fluid mass transfer between dual porosities. Abstract: Local thermal non-equilibrium (LTNE) allows different variations in temperature of three phases: solid skeleton, pore and fracture (fissure) fluids in fractured dual-porosity media. In this work a fully coupled thermo-hydro-mechanical (THM) theory was used to investigate LTNE's effect on thermoporoelastic response around a wellbore. Semi-analytical solutions of three temperatures, two pressures, and effective stresses can be obtained by Laplace transformation. Model results were compared to the numerical results of LTE, which verifies the reliability of the proposed solution. Heat transfer coefficient of solid skeleton-to-pore fluid can be calibrated by a method obtained from the Kozeny-Carman equation. The temperatures of pore fluid and solid skeleton fulfill local thermal equilibrium (LTE) instantaneously in low-permeability geomaterials characterized with large specific surface. However, temperature of fracture fluid differs from those of pore fluid and solid skeleton due to insufficient heat transfer, which cannot be modeled by the LTE models. Besides, the key parameters including the fracture spacing and initial entropy controls heat and fluid mass transfer process, thus influencing the pressures of pore and fracture fluids. Model results showed that LTNE can result in significant difference in effective stress field due to the THM coupling, and then abet the failure potential of the fractured dual-porosity medium positively. Finally, the semi-analytical solutions provide a benchmark for numerical modeling and an evaluation of thermoporoelastic response.